Adaptive Challenges, Adaptive Work, and Adaptive Leadership Among Women Living With HIV in the Southern United States: Findings From a Qualitative Study. (4th May 2022) - Bailey, Donald E.; Caiola, Courtney; Adimora, Adaora A.; Ramirez, Catalina; Holt, Lauren; Johnson, Ragan; Koch, Amie; McGee, Kara; McMillian-Bohler, Jacquelyn M.; Randolph, Schenita D.; Ritchwood, Tiarney D.; Relf, Michael V.
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Women living with HIV have a higher burden of non-AIDS comorbidities and prevalence of chronic conditions. The Adaptive Leadership Framework for Chronic Illness clarifies living with complex health challenges by delineating the technical work of health care providers as well as the adaptive work and leadership behaviors of patients and their providers. We conducted a descriptive, qualitative study of women residing in the Southern United States who were participating in the Women's Interagency HIV Study in North Carolina. Twenty-two participants (mean age = 52.2 years; 90.9% self-identifying as Black or African American) completed semi-structured qualitative interviews. We identified adaptive challenges (e.g., affective and disclosure challenges) and adaptive work and leadership behaviors. Women learned skills to care for their health and support their families and to work with their providers to manage their care. Findings support the importance of identifying leadership behaviors for the purpose of developing person-centered interventions.